Strategi dan Kontekstualisasi Hukum Islam dalam Hukum Nasional: Tipologi Hukum Islam dalam Realitas Sosial-Budaya Perspektif Wael B. Hallaq - Ismasnawati; AM, Rusdi; Karim, Shofwan; Wahyuni, Sri; Yunaldi, Wendra (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
This research discusses the contextualization of Islamic law in the socio-cultural reality in Indonesia. In a diverse society, Islamic law cannot be understood textually alone, but needs to consider social and cultural dynamics. This study highlights five shades of Islam in Indonesia, namely cultural, pluralist, neo-modernist, normative, and nationalist, which shape the character of Islamic legal thought in Indonesia. The contextual approach in Islamic law allows flexibility in the face of changing times without leaving the basic principles of sharia. Based on the perspective of Wael B. Hallaq's perspective, Islamic law must be designed by considering social reality to achieve benefit. This study confirms that contextualization of Islamic law is a must in order to remain relevant and applicable in people's lives. By understanding history and social dynamics, Islamic law can continue to develop as a guideline that suits the needs of the times.